Exploring the Cardioprotective Mechanisms of the Ethyl Acetate Fraction of Vitex cofassus Through Network Pharmacology - Puput Widarini; Ruslin Ruslin; Muhammad Arba (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, with an increasing prevalence each year. The complexity of CVD pathophysiology, which involves multiple biological pathways, required a multitarget therapeutic approach. This study aimed to investigate the potential anti-cardiovascular activity of the ethyl acetate fraction of Vitex cofassus leaves through integrated phytochemical analysis, network pharmacology and molecular docking approaches. The ethyl acetate fraction of Vitexcofassus leaves was analyzed using liquid chromatography-high-resolution mass spectrometry (LC-HRMS), identifying 232 compounds, of which 104 met drug-likeness criteria. Network pharmacology screening revealed 274 potential cardiovascular-related targets. Gene Ontology (GO) analysis highlighted enriched biological processes including responses to oxygen-containing compounds, while cellular component analysis localized target genes primarily to plasma membrane structures, neuron projections, and synapses. Molecular functions were significantly associated with signaling receptor activity and kinase activity, while KEGG pathway analysis further linked Vitex cofassus to key cardiovascular pathways including neuroactive ligand-receptor interactions.The results of Network pharmacology analysis identified SRC, HSP90AA1 and TNF-a proteins as potential targets associated with cardiovascular diseases. Molecular docking studies demonstrated strong binding affinities of selected compounds to HSP90AA1, particularly Compound 74 (-9.703 kcal/mol) and Compound 199 (-9.471 kcal/mol), surpassing the HSP90AA1 native ligand. Similarly, TNF-α binding analysis revealed potent interactions, with Compound 20 (-4.483) and Compound 74 (-4.444) exhibiting superior affinity compared to the native ligand. In conclusion, these findings suggest that Vitex cofassus ethyl acetate fraction contains bioactive compounds with multi-target cardiovascular protective effects, supporting its potential as a therapeutic candidate for cardiovascular diseases.